PENGARUH PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE TERHADAP PENINGKATAN HASIL BELAJAR TEMATIK SISWA SEKOLAH DASAR - Rury Amaliatik, - (2022)
Study results is desired result achieved through the chain process learning. However, not all student get an high results. That's happen because there is student who can't get understand easily. This experiment aim for increasing the results of studies in learning thematic with using the Value Clarification Technique (VCT) model at SDN 1 Tegalmunjul Subdistrict Purwakarta. The research method using pre- experiment with one group pretest-posttest design. The sample on research is students at 4th grade as many as 25 students. Data collection on this research conducted with technical test with questions and non- tests which is observation activity students and documentation, then analyzed using analysis descriptive, T test, simple linear regression test, coefficient test determination and N - Gain. The results showed the use of the VCT model can increase the results on learning thematic class IV SDN 1 Tegalmunjul. The average increased from pretest mean score of 3.8 to 7.08 on the posttest. In addition, the T test produces score 0.000 less significance from 0.05 which means results study student experience has significant difference. Based on simple linear regression test results, obtained score significance 0.000 and obtained coefficient determination (R Square) of 0.662 which means have a big effect on the VCT model on results study student by 66.2%. Then the average of N- Gain of 0.54 which means showing results study experience enhancement medium.